A case of hypoparathyroidism, deafness, and renal dysplasia (HDR) syndrome with a novel frameshift variant in GATA3, p.W10Cfs40, lacks kidney malformation. Issue 12 (14th August 2020) - Kishi, Haruka; Jojima, Teruo; Kogai, Takahiko; Iijima, Toshie; Ohira, Eriko; Tanuma, Dai; Konno, Sachiyo; Kato, Kanako; Kezuka, Atsumi; Akimoto, Kazumi; Sakumoto, Junko; Hishinuma, Akira; et al.
Abstract: Autosomal dominant hypoparathyroidism, deafness, and renal dysplasia (HDR) syndrome are typically diagnosed by manifestations of the three features with a positive family history. Our case carried a de novo variant in causative gene, GATA3, but presenting no renal dysplasia or family history. The phenotypic heterogeneity raises a caution for diagnosis. Abstract : Autosomal dominant hypoparathyroidism, deafness, and renal dysplasia (HDR) syndrome are typically diagnosed by manifestations of the three features with a positive family history. Our case carried a de novo variant in causative gene, GATA3, but presenting no renal dysplasia or family history. The phenotypic heterogeneity raises a caution for diagnosis.